Factors affecting securities prices: Theoretical versus practical approach - Tvaronavičiene, Manuela; Michailova, Julija (Journal of Business Economics and Management, 2006)
Securities market has been influenced by entirety of factors, which roughly could be divided into various groups. In order to show complexity of phenomenon authors strive to overview theories of stock price behaviour. Taking into account, that various authors present rather controversial empirical evidences of certain factors impact on stock’ prices, authors of this paper try to test some relationships practically. Statistical analysis aiming to evaluate quantitatively the dependence of stock index on some chosen statistically measurable factors is being performed. For the latter purpose stock prices of Lithuanian companies and such macroeconomic variables as foreign direct investment, state budget revenue and expenditure, gross domestic product, price index of consumer goods and services, money in a broad sense, average profitability of governmental bonds and inflation have been employed. Firstd Published Online: 14 Oct 2010